2018
DOI: 10.1002/hbm.23999
|View full text |Cite
|
Sign up to set email alerts
|

Inferring distinct mechanisms in the absence of subjective differences: Placebo and centrally acting analgesic underlie unique brain adaptations

Abstract: Development and maintenance of chronic pain is associated with structural and functional brain reorganization. However, few studies have explored the impact of drug treatments on such changes. The extent to which long-term analgesia is related to brain adaptations and its effects on the reversibility of brain reorganization remain unclear. In a randomized placebo-controlled clinical trial, we contrasted pain relief (3-month treatment period), and anatomical (gray matter density [GMD], assessed by voxel-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Tetrault et al [16] found volumetric (and fMRI) changes that are associated with a reduction in pain for knee OA treated with placebo and duloxetine do not overlap within regions of grey matter that are different between participants with OA and non-OA controls. In their recent study in 39 participants with knee osteoarthritis (OA) patients (22 females), randomised to duloxetine (60 mg once daily) or placebo, Tetrault et al [16] showed that outcomes for pain relief were equivalent between treatment groups. The group suggested that distinct circuitry changes in the brain could explain pain relief in each group in brain measures that included grey matter density and resting state fMRI nodal degree count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetrault et al [16] found volumetric (and fMRI) changes that are associated with a reduction in pain for knee OA treated with placebo and duloxetine do not overlap within regions of grey matter that are different between participants with OA and non-OA controls. In their recent study in 39 participants with knee osteoarthritis (OA) patients (22 females), randomised to duloxetine (60 mg once daily) or placebo, Tetrault et al [16] showed that outcomes for pain relief were equivalent between treatment groups. The group suggested that distinct circuitry changes in the brain could explain pain relief in each group in brain measures that included grey matter density and resting state fMRI nodal degree count.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by other groups has suggested a significant negative association between the ‘pain score’ component and regional cerebral blood flow to a right temporal lobe cluster, including the amygdala and the parahippocampal cortex in a study of hand OA [ 15 ]. Tetrault et al [ 16 ] found volumetric (and fMRI) changes that are associated with a reduction in pain for knee OA treated with placebo and duloxetine do not overlap within regions of grey matter that are different between participants with OA and non-OA controls. In their recent study in 39 participants with knee osteoarthritis (OA) patients (22 females), randomised to duloxetine (60 mg once daily) or placebo, Tetrault et al [ 16 ] showed that outcomes for pain relief were equivalent between treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of post-traumatic neuropathic pain patients treated chronically with pregabalin, tramadol, and placebo, Wanigasekera and colleagues were able to differentiate each arm using neuroimaging alone, verify that the placebo mechanism was recruited during the placebo arm by patients, and show that the placebo mechanism was interfered with during the two drug arms (Wanigasekera et al, 2018b). A study in osteoarthritis similarly verifies imaging's ability to infer distinct mechanisms in the absence of subjective differences (Té treault et al, 2018).…”
Section: Biomarker Readouts Of Pharmacodynamic Efficacy Versus Placebomentioning
confidence: 94%
“…If we accept the notion that placebo treatment and individual responses are quantifiable, it is also foreseeable that such treatment induces specific brain adaptations. An idea that was validated recently where we showed that upon completion of a 3‐month period with a placebo or duloxetine treatment, patients with knee osteoarthritis pain underwent differential placebo and active‐drug brain adaptations . More importantly, these different brain adaptations happen despite identical analgesic profile of the two compounds.…”
Section: Prediction Of Placebo Response With Brain Imagingmentioning
confidence: 86%